Peningkatan Kesadaran Dan Partisipasi Siswa Pada Kegiatan Literasi Dalam Pengelolaan Perpustakaan Di SMA Negeri 2 Lubuk Pakam - Monalisa Frince Sianturi; Audy Silvana Br Sinaga; Arnensi Evrinawati Simbolon; May Lisabeth Harianja (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
Community Service (PkM) is a program carried out by FKIP students at HKBP Nommensen University, Medan. Community Service Activities are based on Law of the Republic of Indonesia Number 20 of 2003 concerning the National Education System in Article 20 Paragraph 2 which states that: "Universities are obliged to provide education, research and community service". This Community Service activity focuses on increasing students' awareness and participation in literacy activities. Community Service Activities are a form of contribution from universities in improving the quality of education in society by using an implementation method, namely the direct observation method. By involving students and teaching staff, this activity can have a significant positive impact on literacy development and library management at SMA Negeri 2 Lubuk Pakam. The results of the implementation by considering students' literacy conditions, the role of libraries, the importance of community service activities, increasing awareness and participation of students in literacy activities in library management at SMA Negeri 2 Lubuk Pakam are a strategic and useful initiative to improve the quality of education at the secondary school level above.